CITIZEN PARTICIPATION IN THE BUDGETARY PROCESS - Tenthani, Kizito L. (My University, 2011)
Citizen participation in the budgetary processes in Malawi can be traced back to the PRSP era in the 1990s. This provided a window of opportunity for citizens through civil society organisations to get involved in issues of economic governance. The purpose of this study was to investigate, explore and analyse citizen participation in the budgetary in Malawi. Using qualitative research methodologies, the study interviewed a number of key informants. One of the main findings of the study is that there is some participation of citizens in budget processes for instance through the pre budget consultative meetings. However, it was found that there is room for improvement on the way the pre budget consultative meetings are conducted. Other possibilities for enhancing participation include using members of parliament and operationalising the decentralisation initiative. The study concludes that citizen participation in budgetary process in Malawi remains weak and recommends a number of ways to enhance participation These recommendations include capacitating civil society organisations to enhance their advocacy role and their linkages with the grassroots. The study recommends that the Consolidated Budget Calendar as developed by the Ministry of Finance should be given a binding status, and be popularised. The pre- budget consultative meetings should be improved so that the power balance should not be tilting to the Ministry of Finance.
MM - P&DM
Keywords: Citizen participation; Budget processes; Malawi